Review of the Olethreutes bowmanana-magadana species group, with the description of a new species from the Amur River, Russia (Lepidoptera, Tortricidae) - Dubatolov, Vladimir V.; Bogunova, Anna A.; Nedoshivina, Svetlana V. (Zootaxa, 2014)
We define and review the Olethreutes bowmanana-magadana species group comprised of Olethreutes bowmanana (McDunnough), O. magadana (Falkovitsh), O. kamtshadala (Falkovitsh), and O. pivanica, sp. n., the last from petrophytous sunny slopes in the Amur River. The new species differs from other species of the group by a narrow, triangular-shaped apical process from the sacculus; a round, wide, apical bulb from the cucullus; and a longer, narrow neck of the valva.